A new combination in Handroanthus (Bignoniaceae) from Brazil - Nascimento, Matheus; B. Pastore, José Floriano; R. Zuntini, Alexandre (Phytotaxa, 2024)
While reviewing Vellozo’s Bignoniaceae names in Floræ Fluminensis, a nomenclatural novelty came to light. The name Bignonia longiflora Vellozo, being a later homonym of B. longiflora Cavanilles, was deemed illegitimate. Consequently, Vellozo’s name was eventually replaced with Tecoma speciosa Candolle ex Martius. However, when Tabebuia Gomes ex Candolle was considered the correct genus for this, the final combination ‘Tabebuia speciosa’ was not presented as it was blocked by Tabebuia speciosa Standley (1930). Instead, Tabebuia vellosoi Toledo (1952) was proposed in order to assign a name for Bignonia longiflora Vell. illeg., / Tecoma speciosa DC. ex Mart. Posteriorly, Handroanthus gained broad acceptance as the correct genus and the combination Handroanthus vellosoi (Toledo) Mattos was proposed, bypassing the previously validly published, Tecoma speciosa. However, the latter name holds priority over Tabebuia vellosoi Toledo (≡ Handroanthus vellosoi (Toledo) Mattos), resulting in a new combination, Handroanthus speciosus (Candolle ex Martius) M.Nascim., J.F.B.Pastore & Zuntini, as presented here. This nomenclatural novelty is accompanied by a distribution map, illustration, typification of all involved names, and nomenclatural and taxonomic notes.